Residues, An Alternative for Reducing Water Contamination, Leaching, and Greenhouse Gas Emission - Zohreh Shams; Maryam Heidari; Reza Mokhtari (Agriprima : Journal of Applied Agricultural Sciences, 2023)
This study investigated the efficacy of grape residue in reducing water contamination. Our findings revealed significant reductions in nitrate leaching upon the application of grape residues. Smaller residue particle sizes recorded greater reductions in nitrate leaching compared to larger ones. Utilizing grape waste branches for biochar production offers a sustainable solution, improving water retention, organic matter content, and reducing nutrient leaching. Biochar not only enhances nutrient retention but also promotes microbial activity and nitrogen-fixing bacteria, benefiting soil health and crop productivity. It also helps combat drought and salinity stress. Overall, grape biochar shows potential in mitigating nitrate pollution, enhancing soil quality, and promoting agricultural sustainability. It is important to consider the optimal biochar application rate and particle size to maximize its effectiveness in reducing nitrate leaching while minimizing any potential negative impacts on crop yield. Further research is required to optimize biochar application rates, particle sizes, and long-term effects in diverse agricultural systems. Implementing biochar as a soil amendment holds promise in improving soil health, water quality, and overall sustainability.